Orthotopic bladder substitution: Surgical aspects and optimization of outcomes. Issue 6 (2nd September 2021) - Thakare, N.; Lamb, B. W.; Biers, S.
Abstract: Objectives: Orthotopic bladder substitution (OBS) is a management option for urinary diversion in men and women undergoing cystectomy. The aim of the procedure is to provide a functional continent urinary reservoir of adequate capacity, compliance and low pressure. We have provided a narrative review of the existing literature and highlighted areas where improvement and standardization can be recommended. Methods: Literature search included database search for publications from January 1970 to November 2020, using keywords including OBS, bladder reconstruction, neobladder, radical cystectomy, robotic cystectomy, intracorporeal neobladder, surgical technique, patient selection and outcomes. Results: Due to various factors including indications, operative technique and risk of complications, OBS is an enormous undertaking and commitment for patients, surgeons and health professionals involved in the care pathway. The main considerations for patient selection, the technical elements of the procedure and the rationale behind these are discussed. Previously considered to be a choice for a select few, the inclusion criteria have expanded over the last decade. Similarly, surgical techniques including the choice and configuration of bowel segments, construction of anastomosis and nerve or organ sparing procedures have evolved over the years. Minimally invasive laparoscopic and robotic assisted surgery has added further perspectives to the existing literature on OBS. Understanding the principles of operative techniques and assessing the best evidence to influence patient management is crucial as it has a major impact on clinical outcomes. Peri‐ and post‐operative care, focused on the prevention of complications and morbidity, affects long‐term functional and oncological outcomes, which ultimately dictates the quality of life. Conclusions: This concise overview of OBS literature highlights the importance of pre‐operative, peri‐operative, and post‐operative aspects with regards to the optimization of patient care. To achieve the best results, meticulous attention should be paid in all these areas, surgical and multi‐disciplinary. Patient education and counseling, with shared decision making are central to the success of the procedure.